1981
DOI: 10.1128/aem.41.1.321-322.1981
|View full text |Cite
|
Sign up to set email alerts
|

Differential plating medium for quantitative detection of histamine-producing bacteria

Abstract: A histidine-containing agar medium has been devised for quantitative detection of histamine-producing bacteria that are alleged to be associated with scombroid fish poisoning outbreaks. The responsible bacteria produce a marked pH change in the agar, with attendant color change of pH indicator adjacent to the colonies, thus facilitating their recognition. Proteus morganii and Klebsiella pneumoniae were the two most common histidine-decarboxylating species isolated from scombroid fish and mahi mahi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
1
13

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(118 citation statements)
references
References 3 publications
3
101
1
13
Order By: Relevance
“…Total psychrotrophic aerobic microorganisms were enumerated on plate count agar (PCA) at 20ЊC for 96h (Niven et al, 1981); enterobacteria in violet red bile glucose (VRBG) at 37ЊC for 24h (Anonymous, 1983); enterococci on KF streptococcus agar at 37ЊC for 48h (Anonymous, 1983); slightly halophilic/halotolerant bacteria in TSA plus 3% NaCl at 30ЊC for 48h, moderately halophilic/halotolerant bacteria in TSA plus 10% NaCl at 30ЊC for 96h; and extremely halophilic bacteria in halophilic agar (HA, 25% NaCl) at 30ЊC for 7 days (Baross and Lenovich, 1992).…”
Section: Microbial Analysesmentioning
confidence: 99%
“…Total psychrotrophic aerobic microorganisms were enumerated on plate count agar (PCA) at 20ЊC for 96h (Niven et al, 1981); enterobacteria in violet red bile glucose (VRBG) at 37ЊC for 24h (Anonymous, 1983); enterococci on KF streptococcus agar at 37ЊC for 48h (Anonymous, 1983); slightly halophilic/halotolerant bacteria in TSA plus 3% NaCl at 30ЊC for 48h, moderately halophilic/halotolerant bacteria in TSA plus 10% NaCl at 30ЊC for 96h; and extremely halophilic bacteria in halophilic agar (HA, 25% NaCl) at 30ЊC for 7 days (Baross and Lenovich, 1992).…”
Section: Microbial Analysesmentioning
confidence: 99%
“…Niven's agar was reported to detect with 95.8% and 93.9% accuracy the histamine producers from temperature-abused and bacteria-spiked tuna samples (Chen et al, 1989). Although the differential counts obtained by using Niven's agar were reported to be about 1 log less than that of total aerobic counts on plate count agar in most naturally contaminated scombroid fish samples (Niven et al, 1981), this phenomenon did not occur in this study possibly because the tuna samples were spiked only with one bacterial strain.…”
Section: Bacterial Growth and Histamine Production On Vacuum Packagedmentioning
confidence: 96%
“…It was then steamed at 100°C for 1 hr, filtered, supplemented with 1% glucose, and sterilized at 121°C for 15 min (final pH = 5.7). Niven's differential agar medium (Niven et al, 1981), shown in a previous study (Chen et al, 1989) to accurately detect 95.8% of histamine-producing bacteria on temperature abused tuna, was used to enumerate histamine producing bacteria on tuna samples. The medium was sterilized for 10 min al 121°C to avoid excessive hydrolysis of the agar at the low pH (Niven et al, 1981).…”
Section: Culture Mediamentioning
confidence: 99%
“…Histamine-forming bacteria (HFB) were determined according to the method used by Ko¨se (1993). Total HFB isolation agar contains 0.5% tryptone, 0.5% yeast extract, 2.35% l-histidine-HCl, 0.5% NaCl, 0.006% bromocresol purple, 0.1% CaCO 3 and 2% agar (pH 6.5) (Niven et al, 1981). Mesophilic and psychrophilic HFB were determined using the same condition applied on TVB.…”
Section: Microbial Analysismentioning
confidence: 99%